Effectiveness of Using Kosurasi Media to Improve Basic Math Skills in Children Aged 5-6 Years - Edi Waluyo; Riezky Ayu Saputri (BELIA Early Childhood Education Papers, 2025)
One aspect of development that must be well-stimulated in early childhood is cognitive development. Cognitive development can be stimulated through children’s basic mathematical skills. These skills can be enhanced through the application of Kosurasi media. This study aims to determine the effect of applying Kosurasi media in improving basic mathematical skills in children aged 5-6 years at TK Dharma Wanita Bandung Wonosegoro. This study used a quantitative method with a one-group pretest-posttest research design. The population and sample consisted of 30 children aged 5-6 years at TK Dharma Wanita Bandung. Data collection was conducted through observation, interviews, and documentation. The collected data were analyzed using normality tests, homogeneity tests, paired sample t-test hypothesis testing, and finally, N-gain score tests with the help of the SPSS V.26 data processing application. The average pretest score was 76.10, while the average posttest score was 115.33. A paired sample t-test hypothesis test yielded a significance result of 0.000 < 0.05, indicating that H0 was rejected and Ha was accepted. This means there was a significant difference in the children’s basic mathematical skills before and after the intervention. Furthermore, the N-gain test produced a score of 57.76%, suggesting that the application of Kosurasi media has a moderately effective impact on improving the basic mathematical skills of children aged 5-6 years.